Virulence and enzymatic activity of three new isolates of Beauveria bassiana (Ascomycota: Hypocreales) from the South American locust Schistocerca cancellata (Orthoptera: Acrididae) - Pelizza, Sebastian Alberto (2017)
Schistocerca cancellata is a large-sized acridid, which has historically represented the greatest agricultural problem in southern South America, causing serious economic losses. Since 2015 S. cancellata entered in a state of outbreak condition of historical proportions, producing frequent and large swarms of up to 25 km2 in the north and central region of Argentina and areas of neigh boring Bolivia and Paraguay. At present, chemical insecticides are still the only means available for the control of S. cancellata. We analyzed under laboratory conditions the effectiveness of three fungal strains of Beauveria bassiana isolated from S. cancellata and also determined the relationship between chitinase, protease, and lipase levels at different temperatures of these fungi and their insecticidal activities. The pathogenicity assays were carried out by the sprayed method with concentrations of 1 × 104, 1 × 106 and 1 × 108 conidia/ml. We observed that isolate LPSc 1227 caused the highest mortality at each dose studied, ranging from 100% at a dose of 1 × 108 conidia/ml to 33.3 ± 3.2% at the lowest dose of 1 × 104 conidia/ml. Moreover, in this isolate the highest values of chitinolytic and proteolytic activity were recorded (2.31 ± 0.31 and 1.78 ± 0.04), respectively.